Leakage of the Siemens 160 MLC multileaf collimator on a dual energy linear accelerator - Klüter, Sebastian; Sroka-Pérez, Gabriele; Schubert, Kai; Debus, Jürgen (Physics in medicine and biology, 2011)
Multileaf collimators (MLCs) have been in clinical use for many years and meanwhile are commonly used to deliver intensity-modulated radiotherapy (IMRT) beams. For this purpose it is important to know their dosimetric properties precisely, one of them being inter- and intraleaf leakage. The Siemens 160 MLC features a single focus design with flat-sided and tilted leaves instead of tongue-and-groove. The leakage performance of the 160 MLC was investigated on a dual energy linear accelerator Siemens ARTISTE with 6 MV and 18 MV photon energies. While the intraleaf leakage amounted to nearly the same dose for 6 and for 18 MV, a much higher interleaf leakage for 6 MV was measured. It could be reduced by simply rotating the collimator, and also by changing the voltage applied to the beam steering coils. The leakage of the 160 MLC is shown to be sensitive to beam alignment. This is of special interest for dual energy accelerators, as the two focal spots of both energies, neither in position nor in shape, do not necessarily always coincide. As a consequence of that, a higher leakage can be expected for one out of two energies for the 160 MLC.
Published 22 December 2010
Gesehen am 26.09.2022